WANARA IN RAMAYANA SHADOW PLAY: REPRESENTATION OF HUMANISM, VISUAL COMMUNICATION, AND CONTEMPORARY CULTURE - Febrianto Saptodewo; Sandra Olifia; Iwan Gunawan; Vickrie Ardy (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study explores the representation of Wanara characters in Javanese Wayang kulit Ramayana from the perspectives of Visual Communication Design (DKV), communication science, and humanistic values. Wanara, meaning "forest man" in Sanskrit, symbolizes loyalty, bravery, physical strength, and self-sacrifice for truth, bridging animal instincts and human virtues. The research aims to analyze how visual elements like wanda, sunggingan, and tatahan convey these traits, and their contemporary relevance in Indonesian culture. Employing qualitative methods, including visual semiotics from Peirce, Saussure, and Barthes, the study examines literature, visual documentation, and media adaptations. Findings reveal that Hanoman embodies purity and devotion, Sugriwa leadership and alliance, and Anggada transformation and courage, with these characters persisting in comics, games, and branding. The study highlights Wayang kulit's role in moral education and cultural continuity, offering practical insights for heritage preservation and theoretical contributions to semiotics in traditional arts.